Physician‐ and self‐assessed myasthenia gravis activities of daily living score. Issue 3 (16th November 2017) - Lee, Hye Lim; Min, Ju‐Hong; Seok, Jin Myoung; Cho, Eun Bin; Cho, Hye Jin; Kim, Yong‐Dae; Kim, Byoung Joon
ABSTRACT: Introduction: The Myasthenia Gravis—Activities of Daily Living (MG‐ADL) profile scale is a simple‐to‐use instrument. We aimed to validate this scale in the Korean language and compare physician‐ and self‐assessed MG‐ADL scores (pMG‐ADL‐K and sMG‐ADL‐K). Methods: pMG‐ADL‐K and sMG‐ADL‐K and MG Composite (MGC) scores were obtained from patients. The correlation between pMG‐ADL‐K and MGC and the relationship between the pMG‐ADL‐K and sMG‐ADL‐K were assessed using the Cronbach α and the Spearman coefficient. By intraclass correlation coefficient (ICC), the reliability of each sub‐item of pMG‐ADL‐K and sMG‐ADL‐K was evaluated. Results: We included data from 40 patients. The pMG‐ADL‐K score showed a strong correlation with the MGC score (rho = 0.80, P < 0.01). The Cronbach α was 0.98 between pMG‐ADL‐K and sMG‐ADL‐K, and sub‐items showed good consistency (ICC 0.684–0.985, P < 0.001). Discussion: The MG‐ADL‐K is a valid tool and the sMG‐ADL‐K shows excellent correlation with pMG‐ADL‐K. Both the pMG‐ADL‐K and sMG‐ADL‐K can be used to measure MG severity. Muscle Nerve 57 : 419–422, 2018